2020
DOI: 10.3390/agronomy10060817
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Proline in Screening for Tolerance to Drought and Salinity in Common Bean (Phaseolus vulgaris L.) Genotypes

Abstract: The selection of stress-resistant cultivars, to be used in breeding programmes aimed at enhancing the drought and salt tolerance of our major crops, is an urgent need for agriculture in a climate change scenario. In the present study, the responses to water deficit and salt stress treatments, regarding growth inhibition and leaf proline (Pro) contents, were analysed in 47 Phaseolus vulgaris genotypes of different origins. A two-way analysis of variance (ANOVA), Pearson moment correlations and principal compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 56 publications
5
32
0
4
Order By: Relevance
“…Its application in a metal stress medium led to proline complex formation, reducing metal entry into plant tissues, thus creating more space for the free movement of nutrients [72]. Several studies have highlighted the ameliorative effects of exogenous proline on photosynthetic attributes under stress conditions [42,[44][45][46][47][48]75]. Exogenous proline in stress environments can stabilize the mitochondrial transport chain, enhance rubisco activity in carbon fixation, and thus accelerate the photosynthesis dark reaction [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its application in a metal stress medium led to proline complex formation, reducing metal entry into plant tissues, thus creating more space for the free movement of nutrients [72]. Several studies have highlighted the ameliorative effects of exogenous proline on photosynthetic attributes under stress conditions [42,[44][45][46][47][48]75]. Exogenous proline in stress environments can stabilize the mitochondrial transport chain, enhance rubisco activity in carbon fixation, and thus accelerate the photosynthesis dark reaction [75].…”
Section: Discussionmentioning
confidence: 99%
“…Its exogenous application is also effective in the alleviation of abiotic stresses. Several manuals have highlighted its ameliorative role in various stress environments [42][43][44][45][46]. Shahid et al reported that exogenous proline improved antioxidant enzymes and the water status of pea plants under nickel stress [47].…”
Section: Introductionmentioning
confidence: 99%
“…When plants are exposed to water shortage, the production of proline increases. is increase sometimes reaches 100 times more than the normal synthesis rate [48][49][50][51]. We concluded that the drought-induced change in proline contents in radical and plumule can screen germplasm at the germination stage.…”
Section: Discussionmentioning
confidence: 78%
“…These data strongly support the direct participation of Pro in the mechanisms of salt tolerance in eggplant and related species. Although Pro accumulation in response to salt stress has been observed in many plants, its direct involvement in salt tolerance is not a general feature of Pro-accumulating species since other reports have shown higher Pro contents in the most susceptible genotypes of related species or cultivars of a given species [61]. The accumulation to high concentrations of this osmolyte in wild species has been related to a greater expression or better functioning under stress conditions of the enzyme pyrroline-5-carboxylate synthetase, which has a fundamental role in the biosynthesis pathway of proline [62].…”
Section: Discussionmentioning
confidence: 98%